THE CHALLENGES IN TEACHING SPEAKING USING A COMMUNICATIVE APPROACH AT A BILINGUAL PRIMARY SCHOOL - Evi Karolina Saragih; Lastri Wahyuni Manurung; Jake Muler (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2025)
This study explores the challenges faced in teaching speaking using a communicative approach at a bilingual primary school. The research aims to identify the obstacles teachers encounter while implementing communicative strategies in teaching speaking skills and how these challenges impact students' learning experiences. A qualitative research design was employed, using classroom observations, teacher interviews, and student surveys. The findings reveal that teachers face limited resources, large class sizes, and students' varying language proficiency levels. Moreover, the use of a communicative approach sometimes conflicts with traditional teaching methods that are still prevalent in the school system. Despite these challenges, the research highlights the importance of adapting the communicative approach to suit the bilingual context of the school. The study contributes to the field of education by offering insights into the practical implications of using communicative teaching methods in bilingual settings and provides recommendations for overcoming the challenges identified.